Are the kind of medications and patient's background associated with improving polypharmacy in elderly? - Tomita, Shiori (J Gen Fam Med, 2018)
BACKGROUND: Polypharmacy is associated with negative outcomes in older population. Managing polypharmacy is important but there is no definite method for regulating it. Our aim was to evaluate what medications and patient's background are associated with reducing polypharmacy. METHODS: A prospective, single‐center, cohort study was conducted from June to October in 2016. Participants were 65 and older hospitalized patients. We evaluated the difference between the numbers of medications used at the time of admission and discharge for individual drug class. Univariate analyses using paired t tests were applied to evaluate reduction in prescription medications, and logistic regression was used to evaluate factors for any reduction of prescription medications used at discharge. RESULTS: There were 494 subjects, and the mean of age was 79.6 ± 7.8 years. The mean number of medications used at admission was 6.9 ± 4.7 and that at discharge was 6.8 ± 4.3. The types of medications that reduced between admission and discharge were drugs for functional gastrointestinal disorders and agents acting on the renin‐angiotensin system, etc. Individual components that were strongly associated with a reduction of the number of medications used were only length of hospital stay (OR 0.99, 95% CI, 0.99‐1.0), while the number of medications on admission was related to increasing medication during hospitalization (OR 1.05, 95% CI, 1.01‐1.06). CONCLUSIONS: Most of the kinds and the number of medications prescribed might not be changed during hospitalization despite those were probably the causes of admission. The factor associated with improvements in polypharmacy was length of hospital stay.